KIBRA controls exosome secretion via inhibiting the proteasomal degradation of Rab27a - Song, Lin (Nat Commun, 2019)
Exosomes are nanosized membrane vesicles released from cells after fusion of multivesicular bodies (MVBs) with the plasma membrane (PM) and play important roles in intercellular communication and numerous biological processes. However, the molecular mechanisms regulating exosome secretion remain poorly understood. Here we identify KIBRA as an adaptor-like protein that stabilizes Rab27a, which in turn controls exosome secretion both in vitro and in vivo. Knockdown or overexpression of KIBRA in neuronal and podocyte cell lines leads to a decrease or increase of exosome secretion, respectively, and KIBRA depletion increases MVB size and number. Comparing protein profiles between KIBRA knockout and wild-type mouse brain showed significantly decreased Rab27a, a small GTPase that regulates MVB-PM docking. Rab27a is stabilized by interacting with KIBRA, which prevents ubiquitination and degradation via the ubiquitin-proteasome pathway. In conclusion, we show that KIBRA controls exosome secretion via inhibiting the proteasomal degradation of Rab27a.